2013
DOI: 10.1177/2319510x13519321
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Performance in Strategic Governance and Stakeholder Dimensions: Evidence of Indian Multinational Manufacturing Companies

Abstract: Assessment of corporate social performance has become one of the widely researched areas due to its practical implications. The article assesses the social performance of Indian multinational manufacturing companies on the twin dimensions of strategic governance and responsibility towards primary stakeholders. Using the data collected from corporate social responsibility (CSR) managers through a measurement tool, Indian multinational manufacturing companies have been found to be performing just about average. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…All the control variables used in the present study (size, leverage, age, industry) are significant in contributing to the CSP (Harjoto et al, 2015; Kaymak & Bektas, 2017; Kwatra, 2015). As anticipated, age and size have a significant positive impact on CSP whereas, leverage is negatively related to CSP (Dam & Scholtens, 2012; Haniffa & Cooke, 2005) and there are differences in industry wise CSP.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…All the control variables used in the present study (size, leverage, age, industry) are significant in contributing to the CSP (Harjoto et al, 2015; Kaymak & Bektas, 2017; Kwatra, 2015). As anticipated, age and size have a significant positive impact on CSP whereas, leverage is negatively related to CSP (Dam & Scholtens, 2012; Haniffa & Cooke, 2005) and there are differences in industry wise CSP.…”
Section: Discussionmentioning
confidence: 96%
“…Sometimes, the size of the firm has no relationship with CSP (Kwatra, 2015;McGuire et al, 2003) or it negatively affects CSP or some dimensions of it (Melo, 2012). Kwatra (2015) found that the age of the firm does not affect the CSP of multinational manufacturing companies in India.…”
Section: Control Variablesmentioning
confidence: 99%
See 3 more Smart Citations